HUBUNGAN MOTIVASI BELAJAR TERHADAP MINAT BELAJAR PADA MAHASISWA TINGKAT II DI AKADEMI KEPERAWATAN PANTI KOSALA SURAKARTA - Endang Dwi Ningsih; Rahayu Setyaningsih; Vitha Vidianingrum (Sekolah Tinggi Ilmu Kesehatan Panti Kosala, 2014)
AbstractBackground Motivation is an important role in learning. Motivation empower someone doing activities and it has related with the learning interest. According to the writers observation at the Panti Kosala Nursing Academy Surakarta students, shows that the students have not interested in the learning process which is unparallel with the class attendance performance 100%. Base on the observation, a research done on the second level students of the Panti Kosala Nursing Academy Surakarta. The aim is to know the relation between learning motivation and learning interest of the students. The kind of research was analitical. The research design, correlation and Cross-section approach. The subject were the 97 second level students of the Panti Kosala Nursing Academy Surakarta. The result data were analyzed by Chi-square with P = 0,05 ; P value got : 0,000 < P = 0,05 indicate the Ha value available received (acceptable). The conclusion is having a relation between learning motivation and learning interest on the second level student of the Panti Kosala Nursing Academy Surakarta.Keywords: Motivation and Learning interest